Anticardiolipin in Porphyromonas gingivalis Antisera Causes Fetal Loss in Mice - Schenkein, H.A. (SAGE Publications, 2013)
β2-glycoprotein I (β2GPI)-dependent anticardiolipin autoantibodies (aCl) are associated with thrombosis and fetal loss. Some microbial pathogens can induce pathogenic antibodies cross-reactive with β2GPI. Sera from a significant percentage of periodontitis patients contain aCl, and some periodontal pathogens contain antigens with peptide sequences having homology to β2GPI. We hypothesized that antibodies raised against P. gingivalis (aPg) contain pathogenic aCl that induce fetal resorption. We immunized mice with β2GPI, P. gingivalis W83, or an arg-gingipain-defective mutant of P. gingivalis (HF18). IgG fractions of aPg were immunoabsorbed to remove aCl-like antibodies (abs-aPg). IgG fractions were administered intravenously into tail veins of mated BALB/c females at day 0 of pregnancy. At day 15, the proportions of fetal resorptions were evaluated. The prevalence of fetal loss was significantly greater in the aPg group than in the control IgG group (21.2% vs. 5.3%, p = .001), and greater in the aPg group than in the abs-aPg group (21.2% vs. 12%, p < .05). There were no fetal resorptions observed in the aPgHF18 group (p = .0005 compared with aPg, p = .17 compared with control). aPg antibody contains activity consistent with pathogenic aCl, and the antigen inducing the antibodies that cause increased fetal loss may be on the arg-gingipain protease of P. gingivalis.